Modeling of divertor power footprint widths on EAST by SOLPS5.0/B2.5-Eirene - 邓国忠 刘晓菊 王亮 刘少承 许吉禅 冯威 刘建斌 刘欢 高翔 (Plasma science & technology, 2017)
The edge plasma code package SOLPS5.0 is employed to simulate the divertor power footprint widths of the experimental advanced superconducting tokamak （EAST） L-mode and ELM-free H-mode plasmas.The divertor power footprint widths,which consist of the scrape-off layer （SOL） width λq and heat spreading S,are important physical parameters for edge plasmas.In this work,a plasma current scan is implemented in the simulation to obtain the dependence of the divertor power footprint width on the plasma current Ip.Strong inverse scaling of the SOL width with Ip has been achieved for both L-mode and H-mode plasmas in the forms of λq,L-mode =4.98 × Ip-0.68 and λq,H-mode =1.86 × Ip-1.08.Similar trends have also been demonstrated in the study of heat spreading with SL-mode =1.95 × Ip-0.542 and SH-mode =0.756 × Ip-0.872.In addition,studies on divertor peak heat load and the magnetic flux expansion factor show that both of them are proportional to plasma current.The simulation work here can act as a way to explore the power footprint widths of future tokamak fusion devices such as ITER and the China Fusion Engineering Test Reactor （CFETR）.